Rheology of Ordered and Disordered Symmetric Poly(Ethylenepropylene)--Poly(Ethylethylene) Diblock Copolymers - Rosedale, J H; Bates, F S (Macromolecules, 1990)
A series of poly(ethylenepropylene)--poly(ethylethylene) (PEP--PEE) diblock copolymers, containing 55 vol.% PEP, and the corresponding PEP and PEE homopolymers have been investigated by dynamic mechanical spectroscopy. The ordered and disordered states are characterized by qualitatively different low-frequency rheological properties in close agreement with previous reports on this subject. Three aspects of such behavior in the vicinity of the order--disorder transition are addressed: identification of the microphase-separation transition temperature, T sub MST , evaluation of fluctuation effects, and characterization of the ordering kinetics. T sub MST is identified based on the distinct discontinuity in G' ( omega < < omega exp ' sub c ) and G" ( omega < < omega exp " sub c ) that accompanies the order--disorder transition; omega exp ' sub c approx = 3 omega exp " sub c < < tau exp --1 sub d delineates the beginning of the phase-state-dependent low-frequency regime where tau sub d is the conventional single-chain longest relaxation time. Above and below T sub MST the rheological properties are complex for omega < omega sub c (e.g. failure of time--temperature superposition), owing to the presence of composition fluctuations. In the disordered state these effects are evident 50 deg C beyond T sub MST . The magnitude of these fluctuation effects is underpredicted by recent theory, although the relative fluctuation contributions to the dynamic elastic and loss moduli are in quantitative agreement with theory. Quenching experiments from slightly above to just below T sub MST reveal a approx 10 deg C region within which the ordering process can be followed rheologically. On the basis of the temporal evolution of G' ( omega < < omega exp ' sub c ) following such temperature quenches, it is concluded that the ordering process is governed by heterogeneous (secondary) nucleation. Graphs. 30 ref.--AA